2015
DOI: 10.1016/j.solmat.2014.11.033
|View full text |Cite
|
Sign up to set email alerts
|

Concentrated sunlight for accelerated stability testing of organic photovoltaic materials: towards decoupling light intensity and temperature

Abstract: We have demonstrated OPV accelerated degradation studies using concentrated sunlight, where the atmosphere, temperature and illumination intensity were independently controlled. Testing various schemes for controlling the sample temperature under concentrated sunlight showed that heating of P3HT:PCBM was caused by photons at the absorbed wavelength range and dissipation of excess photon energy, and not necessarily by IR photon absorption. Sunlight chopping was found to be an effective method for independent te… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 56 publications
0
35
0
Order By: Relevance
“…Temperature rise as a result of incident light can occur due to direct absorption from IR, thermalisation losses from other parts of the solar spectrum and absorption by contacts/encapsulants etc. Visoly-Fisher et al showed OPV devices can rise in temperature with exposure to sunlight even with the IR part of the spectrum omitted [30]. The figures for Ross coefficient are slightly lower than those obtained in previous experiments by this group on organic photovoltaic (OPV) modules (0.027 K m 2 /W) and polycrystalline (poly-Si) modules (0.028 K m 2 /W) [9].…”
Section: Effect Of Temperature On Psc Performancementioning
confidence: 71%
“…Temperature rise as a result of incident light can occur due to direct absorption from IR, thermalisation losses from other parts of the solar spectrum and absorption by contacts/encapsulants etc. Visoly-Fisher et al showed OPV devices can rise in temperature with exposure to sunlight even with the IR part of the spectrum omitted [30]. The figures for Ross coefficient are slightly lower than those obtained in previous experiments by this group on organic photovoltaic (OPV) modules (0.027 K m 2 /W) and polycrystalline (poly-Si) modules (0.028 K m 2 /W) [9].…”
Section: Effect Of Temperature On Psc Performancementioning
confidence: 71%
“…At 27 suns intensity, approximately 800 W/m 2 [2] is converted to electrical power, depending on the currentvoltage operating point. The remaining absorbed power of >7 kW/m 2 is dissipated as heat through relaxation of high energy excitations, Joule heating, and absorption in the infrared [14]. Now the open-circuit voltage (V OC ) of the OPV is given by:…”
Section: Discussionmentioning
confidence: 99%
“…We postulate that the introductiono fB ri nto the mixed halide solid solution stressed its structure and induced more structural defects and/org rain boundaries compared to pure halide perovskites, which might be responsible for the accelerated degradation. Accelerated stability tests [6] can rapidlys creen different PV materials and enhancet he development of stable and efficient devices. [1] The structure of such perovskites is AMX 3 ,w here Mi sad ivalent metal cation, Xa re halides, and Ai sa no rganic cation.…”
mentioning
confidence: 99%
“…[3] Nohe tal. Accelerated stability tests [6] can rapidlys creen different PV materials and enhancet he development of stable and efficient devices. [4] Aharone tal.…”
mentioning
confidence: 99%
See 1 more Smart Citation